PENGARUH TONGUE TWISTER TERHADAP PENDERITA CADEL (RHOTACISM): KAJIAN PSIKOLINGUISTIK - Alifah Maulia Ramdani; Lidya Febriani Panjaitan; Namira Aghniya Fatikah Aruman; Shalsavina Aprilianny; Siti Nasywa Nur’naqiyyah Bachtar; Mochamad Whilky Rizkyanfi (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2024)
This study aims to determine the effectiveness of tongue twister training on pronunciation improvement in people with rhotacism using single-subject research (SSR) experimental method. The study involved 7 research subjects and was conducted over a span of 9 days. Data was collected through video and audio recordings of the subjects while they were doing tongue twister exercises. The data collection techniques used were recorded observation techniques and listening-writing techniques. Data analysis was conducted using a qualitative comparative analysis approach. The results showed that the tongue twister exercise positively affected the subjects' pronunciation ability. The subjects showed improvement in pronunciation clarity and accuracy after the practice period. The findings underscore the potential of tongue twister exercises as an effective method in helping individuals with rhotacism improve their pronunciation. This study provides new insights into the treatment of rhotacism, emphasizing the importance of qualitative approaches and fixed comparison analysis in understanding the impact of therapeutic interventions. The practical implications include the development of more individualized and effective speech therapy programs for people with rhotacism.